POTENSI DAYA PEMBANGKIT LISTRIK BIOGAS DI KAMPUNG TERNAK â€œSIDO REJOâ€ SULANG KIDUL, PATALAN, JETIS, BANTUL, YOGYAKARTA - Kurniawati, Dwi Otik; Pristisahida, Adelia Octora (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
The main source of Electricity Energy in Indonesia currently uses fossil fuels, such as oil, coal and others which formation takes a very long time and their use causes pollution. As we know that the supply of fossil fuels in Indonesia in general is running low. The fact shows that since 2004 Indonesia has imported petroleum because domestic oil reserves are insufficient. The electricity installed in most Sulang Kidul residents is 450 VA with an average monthly cost of around Rp. 40,000-Rp. 60,000. The need for electricity usage is still slightly affected by the economic conditions of Sulang Kidul residents who are in the middle to lower levels. Not much household electronic equipment is used. Most residents use electricity only for lighting and television. The potential electricity produced is 23m3x4.7 kWh = 108.1 kWh/day or 3243 kWH/month. With household purchasing power of Rp.930/kWh compared to the average selling price of biogas electricity (of three interest rates) which is still below the purchasing power for household electricity, which is Rp.457.55/kWh. So farmers around Sulang Kidul can afford to buy electricity with the biogas fuel.